Manajemen Kurikulum Pendidikan Karakter Berbasis Nilai-Nilai Keagamaan - Ubaidillah, Aan Eko Khusni (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2019)
Education requires good management including Islamic education. The main aspect of the success of national education is the curriculum. Therefore, good management (management / regulation) of a curriculum is a necessity in achieving educational goals. Curriculum management is a curriculum management system that is cooperative, comprehensive, systemic, and systematic in order to achieve the goals of the curriculum. Character education should be carried out in a planned and measured stage and have a strong foundation, especially religious-based values.